Current threats faced by Neotropical parrot populations. (October 2017) - Berkunsky, I.; Quillfeldt, P.; Brightsmith, D.J.; Abbud, M.C.; Aguilar, J.M.R.E.; Alemán-Zelaya, U.; Aramburú, R.M.; Arce Arias, A.; Balas McNab, R.; Balsby, T.J.S.; Barredo Barberena, J.M.; Beissinger, S.R.; et al.
Abstract: Psittaciformes (parrots, cockatoos) are among the most endangered birds, with 31% of Neotropical species under threat. The drivers of this situation appear to be manifold and mainly of anthropogenic origin. However, this assessment is based on the last extensive consultation about the conservation situation of parrots carried out in the 1990s. Given the rapid development of anthropogenic threats, updated data are needed to strategize conservation actions. Using a population approach, we addressed this need through a wide-ranging consultation involving biologists, wildlife managers, government agencies and non-governmental conservation organizations. We gathered up-to-date information on threats affecting 192 populations of 96 Neotropical parrot species across 21 countries. Moreover, we investigated associations among current threats and population trends. Many populations were affected by multiple threats. Agriculture, Capture for the Pet Trade, Logging, each of them affected > 55% of the populations, suggesting a higher degree of risk than previously thought. In contrast to previous studies at the species level, our study showed that the threat most closely associated with decreasing population trends is now Capture for the local Pet Trade. Other threats associated with decreasing populations include Small-holder Farming, Rural Population Pressure, Nest Destruction by Poachers, Agro-industry Grazing, Small-holder Grazing, and Capture for the international Pet Trade. Conservation actions have been implemented on < 20% of populations. Our results highlight the importance of a population-level approach in revealing the extent of threats to wild populations. It is critical to increase the scope of conservation actions to reduce the capture of wild parrots for pets.